Model-Driven Software Migration: A Methodology Reengineering, Recovery and Modernization of Legacy Systems - Wagner, Christian (Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2014)
Today, reliable software systems are the basis of any business or company. The continuous further development of those systems is the central component in software evolution. It requires a huge amount of time-, man power- as well as financial resources. The challenges are size, seniority and heterogeneity of those software systems. Christian Wagner addresses software evolution: the inherent problems and uncertainties in the process. He presents a model-driven method which leads to a synchronization between source code and design. As a result the model layer will be the central part in further evolution and source code becomes a by-product. For the first time a model-driven procedure for maintenance and migration of software systems is described. The procedure is composed of a model-driven reengineering and a model-driven migration phase. The application and effectiveness of the procedure are confirmed with a reference implementation applied to four exemplary systems. Contents Theoretical Context Description of the Methodology Case Study Applications Evaluation of Results Target Groups Researchers and students in the field of computer science, information management and commercial information technology Practitioners in the field of software development, IT-Managers, CIOs The Author In 2012, Dr.-Ing. Christian Wagner finished his PhD thesis at the University of Potsdam, Chair of Service and Software Engineering. Currently, he is working as System-Analyst in the automotive sector.  .